2015
DOI: 10.5327/z2447-2115201500010004
|View full text |Cite
|
Sign up to set email alerts
|

Perfil de idosos votantes no Rio Grande do Sul

Abstract: Pouco se sabe sobre a participação cívica da pessoa idosa no Brasil, por isso propôs-se investigar os fatores associados à participação dos idosos nas eleições presidenciais de 2010. MÉTODOS: Foram analisados os dados do inquérito epidemiológico, transversal e observacional realizado no período de 2010 a 2011, com 7.315 idosos identificados por visita domiciliar usando amostragem aleatória dos setores censitários de 59 cidades do Estado do Rio Grande do Sul, Brasil. Análise de regressão logística usou como var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Such practices should focus on the prevention of sexually transmitted diseases so that the elderly can use barrier methods naturally. 13 The study titled "The profile of the elderly population living in Rio Grande do Sul State", 15 which was carried out with 7,315 elderly people, showed that 35% reported having sex. Nonetheless, only 3.9% reported always using condoms, 3% reported using them sometimes, and 25.5% reported not using them because they considered them harmful, unnecessary or the partner did not like them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such practices should focus on the prevention of sexually transmitted diseases so that the elderly can use barrier methods naturally. 13 The study titled "The profile of the elderly population living in Rio Grande do Sul State", 15 which was carried out with 7,315 elderly people, showed that 35% reported having sex. Nonetheless, only 3.9% reported always using condoms, 3% reported using them sometimes, and 25.5% reported not using them because they considered them harmful, unnecessary or the partner did not like them.…”
Section: Discussionmentioning
confidence: 99%
“…The most cited group involved answers related to risk situations/risk groups. In this case, 22 (58%) physicians pointed out the following situations that increased the risk of HIV contamination: safe or unsafe sex (15), drug users (eight), street people (four), alcohol abuse (two), same-sex sexual behavior (one), sex with HIV-positive partners (one), indigenous people (one), and prisoners (one).…”
Section: "Lack Of Focus On This Search By Professionals Who Focus On the Other Demands Of Elderly Patients The Elderly Also Does Not Seekmentioning
confidence: 99%